1986
DOI: 10.1093/ptj/66.9.1382
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gait of Young Women and Elderly Women

Abstract: The purpose of our study was to describe and compare free-speed gait patterns of healthy young women with healthy elderly women. The evaluation was completed with high-speed cinematography using synchronized front and side views of 26 healthy volunteers. One group was composed of 13 subjects 20 to 35 years of age, and the other group was composed of 13 subjects 60 to 84 years of age. Each subject participated in one test session consisting of three filmed trials of free-speed ambulation down a 14-m walkway. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
79
2
8

Year Published

1990
1990
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(97 citation statements)
references
References 0 publications
8
79
2
8
Order By: Relevance
“…In agreement with the previous studies (Dobbs et al, 1993;Hageman and Blanke, 1986;Himann et al, 1988;Imms and Edholm, 1981;Rubenstein et al, 1988;Murray et al, 1969;Wall et al, 1991;Trueblood and Rubenstein, 1991), our studies indicated that older adults walked slower than younger adults(120.22cm/s±10.12 Vs 133.23cm/s±11.59). There have been many suggestions for why older adults walk slower.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with the previous studies (Dobbs et al, 1993;Hageman and Blanke, 1986;Himann et al, 1988;Imms and Edholm, 1981;Rubenstein et al, 1988;Murray et al, 1969;Wall et al, 1991;Trueblood and Rubenstein, 1991), our studies indicated that older adults walked slower than younger adults(120.22cm/s±10.12 Vs 133.23cm/s±11.59). There have been many suggestions for why older adults walk slower.…”
Section: Discussionsupporting
confidence: 93%
“…Slow walking speed in the elderly has been reported in many previous papers (Murray et al, 1969;Hageman and Blanke, 1986;Himann et al, 1988;Kaneko et al, 1991), and this slowness has been found to be mainly caused by short stride length (Imms and Edholm, 1981;Ferrandez et al, 1990;Nishizawa et al, 2000). Over the last century, differences in height have been observed between cohorts in developed countries (Kouchi, 1996).…”
Section: Discussionmentioning
confidence: 88%
“…A adoção de estratégias adaptativas no andar do idoso surge mediante a necessidade de compensar os déficits neuromusculares, como, por exemplo, a diminuição da velocidade, menor comprimento de passo, redução do tempo da fase de balanço e diminuição dos movimentos articulares do quadril, joelho e tornozelo (HAGEMAN et al, 1986;JUFGE;DAVIS;OUNPUU;1996;CHEN et al, 1991;HORTOBÁGYI, 2000;CHOU, 2004;CHOU, 2005;HORTOBÁGYI et al, 2009). Haja vista que a marcha não pode ser considerada um ato reflexo e sim um processo que requer associação de respostas cognitivas para gerar uma execução adequada, objetivamos com o presente estudo analisar a influência do medo de cair e da dupla tarefa sobre a variabilidade de variáveis cinemáticas e eletromiográficas da marcha de idosos para compreender os efeitos de sobrecargas relacionadas à tarefa durante o processo de deambulação (LUNDIN-OLSSON; NYBERG; GUSTAFSON, 1997;BEAUCHET et al, 2003;SALAMON;PRIEST, 2004).…”
Section: Discussionunclassified